Impersonal experiential constructions in ancient Northwest Semitic languages in a diachronic perspective - Notarius, Tania (Journal of Semitic studies, 2025)
This paper scrutinizes the impersonal usage of experiential constructions in ancient Northwest Semitic (NWS) languages. A methodological distinction is made between affective and evaluative types of the impersonal experiential usage, where the affective type communicates the physical and emotive condition of the Experiencer (Hebrew ḥam lô ‘he feels warm’), and the evaluative type communicates an attitude towards particular proposition (Hebrew ˀim ˁal PN ṭôḇ ‘if PN would like …’). These types are distributed differently in the ancient NWS languages. The Old Canaanite of El-Amarna demonstrates both usages of the impersonal experiential construction, while Akkadian has only the evaluative usage. Ugaritic avoids the impersonal usage, except for some diagnostic cases in the language of prose. Biblical Hebrew consistently demonstrates both types. Official Aramaic exemplifies the evalua tive type only, while the affective type emerges at the Middle and Late Aramaic stages. In this paper, it is hypothesized that the impersonal experiential construction, and its affective type in particular, may be an areal Canaanite feature. The affective experiential usage appears in Ugaritic and then a thousand years later in Aramaic, as a result of contact with Canaanite languages.